The influence of three-aircraft formation blinking jamming on the performance of ground monopulse radar - Zhaozheng Liu; Xing Wang; Zelong Hao; Weijie Kang; You Chen (AIP Advances, 2023)
The purpose of this study is to evaluate the jamming effectiveness evaluation against monopulse radar when using a non-coherent blinking jamming model at regular intervals based on three aircraft flight trajectories. To begin, the formation trajectory is solved under various aircraft attitudes to provide the radar cross section model for three-aircraft formation flying. Following that, the jamming angle tracking error model for three-aircraft formation flying is built and coupled with the features of monopulse radar angle tracking. The effective decoy angle and other criteria are used to measure the variance in jamming performance and the efficacy of formation flying radar jamming under varying jamming power and jamming gain. Finally, using the jamming effectiveness assessment criterion, the jamming effectiveness of formation flight is calculated. The findings demonstrate that the three-aircraft formation based on time transformation jamming model can successfully induce the monopulse radar angular tracking error, enhance it to 1.54 times, and stabilize the jamming effectiveness at 0.84, and it also has a relatively good jamming effect under straight flight trajectory and circular flight trajectory. Our jamming strategy will contribute to the design of electronic countermeasures, of which the findings of this research have practical significance for the application of new jamming styles.